PELESTARIAN BUDAYA NUSANTARA INDONESIA MELALUI TARI KREASI DI SANGGAR BIMBINGAN RAWANG, SELANGOR MALAYSIA - Hernawati, Nina; Hadiana, Oman; Abdul Manan, Nanan; Astria Nur, Hana; Heriyana, Tio (Gapenas Publisher, 2025)
As Indonesian citizens, it is appropriate for us to protect and preserve the existing culture of the archipelago, both in remote areas and in cities. Don’t forget the children of Indonesian citizens who live in Malaysia, they need to be introduced to the archipelago culture that belongs to their own country, Indonesia. The culture of the Indonesian archipelago that is very inherent and needs to be inherited and taught from an early age is the art of dance. This service activity was carried out at the Rawang Guidance Studio, Selangor Malaysia. The aim of this service is to provide knowledge and teaching of the art of dance to students in foreign countries, because they want to give birth to the next generation to preserve the nation’s culture, as well as foster students’ interest and talent in the art of dance. The method for implementing creative dance teaching is preparation, analysis of dance teaching design, implementation and evaluation. The activities carried out include the introduction of regional songs, teaching basic dances and evaluation in the form of art performances.